The Implementation Of Borrowing Money Agreement With The Guarantee Of Movement Object In PT. Pegadaian (Persero) Branch Of Subang Based On Act No. 42 Of 1999 On Fiduciary - Erwin Marlina; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The purpose of this research is to know and understand the implementation of the agreement to borrow against moving objects Pegadaian of Subang district connected by Act No. 42 of 1999 on Fiduciary, and the constraints faced by Pegadaian of Subang district in the implementation of the agreement to borrow money secured against moving objects associated with Act No. 42 Of 1999 regarding Fiduciary, and solutions. Based on the results of data analysis can be concluded that: First,Implementation of the Money Lending and Borrowing Agreement with the guarantee of Moving Bodies PT. Pegadaian (Persero) is not in accordance with the provisions of Article 1320 and Article 1338 of the Civil Code, as the substance of the agreement is determined unilaterally by PT. Pegadaian (Persero) and very burdensome customers, whereall costs related to the disbursement of the loan and the auction process is borne by the customer, including if the customer requires registration, fiduciary, but most refused to register fiduciary because of the extra charge (additional costs to be borne by the customer and the need for immediate disbursement of credit requires a long time. this is contrary to Act No. 42 Of 1999 regarding Fiduciary. Secondly, the constraint faced by PT. Pegadaian (Persero) Branch of Subang in the Implementation Agreement with Collateral Borrowing Money on Moving objects are need customers defaulting party (broken promises). One type of breach committed by the debtor PT. Pegadaian (Persero) Branch of Subang is overdue, the delay in the implementation of the payment obligations on time specified in the agreement lending and borrowing. Solution by PT. Pegadaian (Persero) Branch of Subang is doingpersuasive efforts, Somasi (warning), withdrawal and auction the collateral in accordance with Act No. 42 of 1999 on Fiduciary.Keywords: Implementation Agreement; Moving Objects Guarantee; PT Pegadaian.